Love it when you speak foreign: A trans-national perspective on the professional development of doctoral supervisors in South Africa - Bitzer, Eli; Trafford, V N; Leshem, S (South African Journal of Higher Education, 2016)
Being a successful doctoral supervisor and adhering to international requirements and contexts involve important qualities. Being knowledgeable in disciplines and understanding different methodologies, being sensitive to cultural diversity and cultivating interpersonal relationships are examples. As doctoral candidates and their supervisors carry major responsibilities, doctoral quality and success are associated with several challenges. This paper explores some of these challenges and suggests that candidates and supervisors might contribute more substantially to new knowledge if international quality measures for theses and ‘doctorateness’ (or ‘doctoralness’) are considered. This explorative study reports descriptive and analytical findings from a project in South Africa whereby three senior academics from three countries collaborated and acted as facilitators of research and developmental efforts concerning doctoral education and the professional development of supervisors. Such efforts involved both supervisors and doctoral candidates – the latter whose views are seen as important to shape supervisors’ views of their own supervisory practices and standards for the doctorate. The paper outlines the processes and feedback from a series of developmental opportunities that were created and provides guidelines as to how trans-national efforts – particularly, but not exclusively, in the context of a developing country – can be used to promote doctoral education and supervisor professional development.